THREE MAINSTREAM OF FEMINISM: THEORY OF LIBERAL, MARXIST AND RADICAL FEMINISM - Erkan DİKİCİ (Fırat University, 2019)
The emergence of feminism concept defined as women's struggle for freedom and equality are based on the 18th century. Feminism, the women's movement as possible, describe how each has changed over time the perception of feminism. The impact of industrialization and ideological movements have been the main reason for this change. Changes in the feminist movement began to move away from understanding the processes that occur. The feminist movement with emphasis on gender equality in the context of gender, is composed of first-wave feminists. After referred to as liberal feminism feminist, it comes the second wave feminists drew attention to sexuality and biological